2018
DOI: 10.21248/fvss.21.56
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation structurale de la végétation ligneuse du Parc National de Mozogo-Gokoro (Cameroun)

Abstract: La gestion forestière durable est étroitement dépendante de la compréhension de la dynamique structurale. Cette étude vise la description de la structure de la végétation ligneuse du Parc National de Mozogo-Gokoro, situé en zone soudano- sahélienne au Cameroun. À l’issue d’un inventaire floristique, prenant en compte tous les individus ligneux, les analyses ont porté sur les paramètres suivants: la structure diamétrale, les types de tiges, la répartition en classes de hauteurs, les types biologiques et les typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The distribution of diameter classes is another important indicator involved in the structural study of vegetation, its evolutionary trend and regeneration dynamics (Sandjong, 2018). Diameter structures are indicative of Composition, taxonomic structure, and diversity index were calculated using Microsoft Excel 2010 software and XLSTAT 2016 software was used for linear regressions between diameter and height.…”
Section: -3-7 Diameter Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of diameter classes is another important indicator involved in the structural study of vegetation, its evolutionary trend and regeneration dynamics (Sandjong, 2018). Diameter structures are indicative of Composition, taxonomic structure, and diversity index were calculated using Microsoft Excel 2010 software and XLSTAT 2016 software was used for linear regressions between diameter and height.…”
Section: -3-7 Diameter Structurementioning
confidence: 99%
“…This indicates that large individuals are highly exploited as noted by Idrissa et al (2020). This type of form is characteristic of multi-species stands with a predominance of young individuals ensuring a high regeneration potential (Sandjong, 2018). The predominance of young individuals can be explained by the relationship between species temperament and height distribution (Kouyate et al, 2020).…”
Section: -4 Vegetation Types Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, numerous studies carried out in the Sahelian and Sudanian zones have also confirmed this structural variability of species (Rabiou et al, 2015;Idrissa et al, 2017;Amadou et al, 2020). According to Sandjong et al (2018), adaptations to ecological conditions, competition for resources and exploitation would underlie this structural variability. The low presence of adult individuals with a diameter greater than 15 cm was observed in species with an inverted Jshape that embodies secure regeneration.…”
Section: Horizontal Structure Of Edible Fruit Treesmentioning
confidence: 99%